Phonetic events from the labeling the european Portuguese database for speech synthesis, FEUP/IPB-DB - Teixeira, João Paulo (2011)
In this paper a labeled new speech signal database (FEUP/IPB-DB) in Standard European Portuguese (hereafter SEP) is presented. The objective of this work is, on one hand, to provide phonetic material for Text-to-Speech (TTS) systems construction, either from the start or to improve the quality of existing ones, and, on the other hand, to place at service of the SEP scientific community a phonetically and prosodically valuable speech corpus, essential for Speech Synthesis or Phonetics research. Our purpose is to make it available for the scientific community, since there isn’t any other DB of its kind for EP. The main features of the database will be described as well as some basic statistical aspects. A discussion of some methodological problems and some observed phenomena in experimental phonetics deriving from the speech signal labeling is also done. The approach in our work is to produce a resource that can be further improved in subsequent steps with minimal re-work. The phonetic, linguistic and technical consistency are guaranteed through the involvement of a multidisciplinary team.